Role of the fungus-specific flavin carrier Flc1 in antifungal resistance in the fungal pathogen Cryptococcus neoformans. (14th July 2018) - Zhang, Ping; Li, Chenxi; Huo, Liang; Xiang, Biyun; Rahim, Kashif; Hao, Xiaoran; Zhu, Xudong
Abstract: FLC family, a conserved fungus-specific family of integral membrane proteins, has been demonstrated to play important roles in flavin transport, growth, and virulence in several fungi but not yet in Cryptococcus neoformans . In this study, we have identified the single homologue of flavin adenine dinucleotide transporter in the opportunistic pathogen C. neoformans . The computational and phylogenetic analysis confirmed the fungal specificity of cryptococcal Flc1 protein, thus providing a promising drug target for clinical treatment of cryptococcosis. Disruption of FLC1 conferred sensitivity to 1% Congo red and 0.02% SDS, as well as leading to impaired chitin distribution in cell wall as observed with Calcofluor White staining, which collectively indicated the roles of FLC1 in maintenance of cell wall integrity. Further investigations revealed the defects of flc1Δ mutant in resistance to poor nutrition and elevated temperatures, and the ability to undergo invasive growth under nutrient-depleted conditions was reduced as well in flc1Δ mutant, suggesting the roles of Flc1 in response to environmental stresses. More importantly, our results showed that flc1Δ mutant exhibited severe susceptibility to antifungal aminoglycosides (hygromycin B and geneticin) and amphotericin B, but developed multidrug resistance to flucytosine and rapamycin, which provided great hints for therapeutic failure of cryptococcosis in clinic with the standard combination therapy. Finally, typical virulence factors including melanin biosynthesis and capsule formation in flc1Δ mutant were reduced as well, indicating the possible involvement of Flc1 in virulence.